Analisis Sumber Risiko Produksi Pakcoy dengan Menggunakan House Of Risk (Studi Kasus Sintesa Farm Lembang, Kabupaten Bandung Barat) - Faujiah, Sifa; Pardian, Pandi; Syamsiyah, Nur; Rasmikayati, Elly (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Sintesa Farm faces challenges in meeting the demand for pakcoy from distributors, as well as difficulties in maintaining product conformity to the specified standards. These problems are caused by various risks in production activities. This study aims to identify risk agent in pakcoy production at Sintesa Farm. This research uses a qualitative method with case study approach and the House of Risk (HoR) analysis. The results reveal that 12 out of 24 risk agent are classified as priority risk agent and contribute 80.9% to the overall identified risks. The risk source with the highest Aggregate Risk Potential value is attacked by root gall disease. The discrepancy in work procedures with the pakcoy production standard at Sintesa Farm was caused by the suboptimal implementation of the controlling function, which led to various risks caused by human resources.